Design of gaming material for the transformation of the role of students of middle childhood - Moreno-Arverás, Michelle (2019)
The objective of the project contemplated the design of a mediator that would modify the role of the middle childhood students from passive to active during the learning process. The IDEO kit: Design Thinking for Educators was used due to its characteristic innovation centered on people, allowing to easily detect needs and solve them, appealing to the sensibility and empathy of the designer. A separate game material was generated in stages of familiarization and difficulty, where children can experiment with their own rules and invest their role in the learning process, being them knowledge-sharing, not just receptors. The material was well received, with the first two stages being more popular in the first ages of middle childhood and the third stage for older children.